2016
DOI: 10.1107/s2053230x15023390
|View full text |Cite
|
Sign up to set email alerts
|

New crystal form of human ubiquitin in the presence of magnesium

Abstract: Ubiquitin is a small globular protein that has a considerable number of lysine residues on its surface. This results in a high surface entropy that precludes the formation of crystal-packing interactions. To date, only a few structures of the native form of ubiquitin have been solved, and most of the crystals that led to these structures were obtained in the presence of different divalent metal cations. In this work, a new crystallographic structure of human ubiquitin solved from crystals grown in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Ubiquitin (Ub) is a small protein (76 amino acids) in different organisms, which plays crucial roles in degradation of misfolded proteins via the ubiquitin proteasome system (UPS), and maintains the protein homeostasis in living cells [50]. Although Ub is not a metalloprotein, crystallographic studies showed that various divalent metal ions potentially bind to the protein, such as Cu 2+ , Zn 2+ , Cd 2+ and Hg 2+ [51], as well as Mg 2+ [52]. Using molecular modeling and dynamics simulations, Lin and co-workers showed that two surface residues of Ub, Glu18 and Asp21, may coordinate to UO 2 2+ , as well as water molecules ( Figure 2d) [53].…”
Section: Binding To Potential Metal-binding Sitesmentioning
confidence: 99%
“…Ubiquitin (Ub) is a small protein (76 amino acids) in different organisms, which plays crucial roles in degradation of misfolded proteins via the ubiquitin proteasome system (UPS), and maintains the protein homeostasis in living cells [50]. Although Ub is not a metalloprotein, crystallographic studies showed that various divalent metal ions potentially bind to the protein, such as Cu 2+ , Zn 2+ , Cd 2+ and Hg 2+ [51], as well as Mg 2+ [52]. Using molecular modeling and dynamics simulations, Lin and co-workers showed that two surface residues of Ub, Glu18 and Asp21, may coordinate to UO 2 2+ , as well as water molecules ( Figure 2d) [53].…”
Section: Binding To Potential Metal-binding Sitesmentioning
confidence: 99%
“…Of interest, both Cd and Zn are group IIb metals that share a common affinity for sulfhydryl groups and likely the same molecular targets. By displacing Zn, one might assume from the so-called ionic mimicry concept that Cd would inhibit the Zn-dependent enzymes, disturb folding of Zn-domain, and interfere with Zn-regulated physiological processes [28,[56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…As Cd and Zn are in the same group of the chemical periodic table, it can be inferred from the so-called ionic mimicry concept that Cd may share with Zn the same targets [28,56]. In this regard, Cd is able to replace Zn and binds to ubiquitin [57,58], Zn finger domains, and the SH group within the active sites of ubiquitin ligases and deubiquitinases [59], a property that may help explain the dramatic upregulation of ubiquitination. However, the results of in vitro assays using free tetraubiquitin suggested that the addition of Cd (5 µM) had little, if any, direct effect on the activity of the ubiquitin ligases and deubiquitinases (Figure 3E,F).…”
Section: Is An Activator Of K63-linked Ubiquitination In Lung and Renal Cellsmentioning
confidence: 99%
“…The counterions from set 1 of additive mixes such as sodium, potassium and others (Table 1) can alter the physico-chemical properties of proteins in solution (Bostro ¨m et al, 2011;Medda et al, 2012;Salis & Ninham, 2014;McPherson, 2001). Additionally, they can facilitate crystallization through the media-tion of contact sites, especially with divalent metal cations (Camara-Artigas et al, 2016;Hegde et al, 2017). The additives from set 2 (Table 2) are more likely to alter protein-water interactions (Timasheff, 2002) than be part of the crystal structure.…”
Section: Morpheus Additive Mixes Integrated Into Fusionmentioning
confidence: 99%